Carbon-ceramic brake disc and preparation method thereof, brake system and vehicle

By designing stacked transition layers and functional layers in the carbon ceramic brake disc, using silicon carbide/carbon/metal composite materials to improve the friction coefficient and extend the service life, the problems of easy cracking and insufficient friction coefficient of the carbon ceramic brake disc are solved, and the problems of carbon ceramic brake discs are improved. The reliability and performance of the brake system.

CN119308950AActive Publication Date: 2025-01-14BYD CO LTD
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202310864890.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-14
Estimated Expiration
2043-07-13

AI Technical Summary

Technical Problem

The carbon ceramic brake disc is prone to cracking after multiple braking, resulting in insufficient service life and reliability, and limited friction coefficient with the metal friction plate, affecting the performance of the brake system.

Method used

A carbon ceramic brake disc is designed, which includes a bearing layer and a friction layer. The friction layer is composed of a layered transition layer and a functional layer. The transition layer is close to the bearing layer. The functional layer contains silicon carbide/carbon/metal composite material, and the metal is Metals that can form solid solution with carbon are designed to increase friction coefficient and reduce stress concentration and extend service life.

Benefits of technology

It improves the metal friction coefficient and service life of the carbon ceramic brake disc, enhances the reliability and braking effect of the brake system, reduces the loss of friction plates during high-speed braking, and extends the service life of the overall brake system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119308950A_ABST
    Figure CN119308950A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-ceramic brake disc and a preparation method thereof, a braking system and a vehicle. According to the carbon-ceramic brake disc, due to the special structure, the carbon-ceramic brake disc is not prone to cracking in the using process, has the high metal friction coefficient, and can have the long service life and the high reliability at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of brake materials, and in particular to a carbon-ceramic brake disc and a preparation method thereof, a brake system and a vehicle. Background Art

[0002] At present, carbon-ceramic brake discs are gradually attracting attention due to their advantages such as low density, high strength and high hardness. However, carbon-ceramic brake discs are generally obtained by directly siliconizing carbon fibers / carbon porous bodies. The carbon-ceramic brake discs made in this way are prone to cracking after multiple braking, resulting in brake disc failure, which seriously limits the service life and reliability of the brake discs.

[0003] In addition, when the brake disc is applied to the brake system, the friction plate in the brake system clamps the two surfaces of the brake disc to stop the rotation of the brake disc. Generally, the composition of the friction plate includes metal, and the friction coefficient between the carbon-ceramic brake disc and the metal is limited. Braking at high speed will cause great damage to the metal friction plate, which is not conducive to the service life of the brake system and the braking effect. Therefore, it is urgent to provide a carbon-ceramic brake disc with a special structural design to improve the metal friction coefficient of the carbon-ceramic brake disc and give it a longer service life. Summary of the invention

[0004] In view of this, the present application provides a carbon-ceramic brake disc. Due to its special structure, the carbon-ceramic brake disc is not easy to crack during use and has a higher metal friction coefficient, and can have both a longer service life and higher reliability.

[0005] In a first aspect, the present application provides a carbon ceramic brake disc, comprising a bearing layer and a friction layer arranged on two opposite sides of the bearing layer; the friction layer comprises a transition layer and a functional layer arranged in a stacked manner, and the transition layer is close to the bearing layer;

[0006] Among them, the bearing layer comprises a carbon / silicon carbide composite material; the transition layer comprises a silicon carbide / carbon composite material, and the volume percentage of silicon carbide in the transition layer is greater than the volume percentage of silicon carbide in the bearing layer; the functional layer comprises a silicon carbide / carbon / metal composite material, wherein the metal is a metal that can form a solid solution with carbon.

[0007] A functional layer and a transition layer are provided in the friction layer of the above-mentioned carbon-ceramic brake disc. The functional layer has good wear resistance and a high metal friction coefficient. At the same time, the transition layer can reduce the composition difference between the functional layer and the bearing layer, thereby reducing the cracking caused by excessive stress of the brake disc during braking, thereby extending the service life of the brake disc and improving its reliability.

[0008] Optionally, a volume ratio of the silicon carbide to the carbon in the functional layer is greater than a volume ratio of the silicon carbide to the carbon in the transition layer.

[0009] Optionally, the friction layer includes n unit layers stacked together, wherein the n unit layers include a unit layers constituting the transition layer and b unit layers constituting the functional layer; n is a positive integer greater than or equal to 2, a and b are each independently a positive integer, and a+b=n;

[0010] I i+1 >I i ; Among them, I i Represents the proportion of the volume of the silicon carbide in the i-th unit layer in the sum of the volumes of the silicon carbide and the carbon; wherein the i-th unit layer is any one of the 1st unit layer to the (n-1)th unit layer, and the 1st unit layer is arranged close to the bearing layer, 1≤i≤n-1, and i is a positive integer.

[0011] Optionally, 5% ≤ I i+1 -I i ≤20%.

[0012] Optionally, the thickness of each unit layer is independently in the range of 0.4 mm to 1.0 mm.

[0013] Optionally, the friction layer has a thickness of 3.0 mm to 6.0 mm.

[0014] Optionally, the thickness of the transition layer is 2.0 mm to 5.0 mm; the thickness of the functional layer is 1.0 mm to 3.0 mm; and the thickness of the bearing layer is 30.0 mm to 50.0 mm.

[0015] Optionally, the metal is dispersed in the functional layer in the form of powder, and the D50 particle size of the powder is in the range of 0.5 μm to 20 μm.

[0016] A second aspect of the present application provides a method for preparing a carbon-ceramic brake disc, comprising the following steps:

[0017] (1) Providing a carbon fiber preform, the carbon fiber preform comprising carbon fiber impregnated with a first slurry, wherein the first slurry contains carbon powder; forming at least one unit layer preform on two opposite sides of the carbon fiber preform, so that the unit layer preform is connected to the carbon fiber preform; wherein the unit layer preform comprises carbon fiber cloth; during the forming process, injecting a second slurry into the unit layer preform; the second slurry comprises carbon powder and silicon carbide powder, to obtain a first preform;

[0018] (2) continuing to form at least one unit layer preform on the opposite side surfaces of the first preform; wherein, during the forming process, a second slurry containing metal powder is injected into the unit layer preform to obtain a second preform; the metal powder is a metal powder that can form a solid solution with carbon;

[0019] (3) After the second preform is carbonized, it is subjected to chemical vapor deposition carbon treatment, and then high-temperature heat treatment and siliconization treatment are performed in sequence to transform the carbon fiber preform into a bearing layer of a carbon / silicon carbide composite material, transform the unit layer preform injected with the second slurry into a transition layer, and transform the unit layer preform injected with the second slurry added with metal powder into a functional layer, so as to obtain a carbon-ceramic brake disc; wherein the transition layer comprises a silicon carbide / carbon composite material, and the volume percentage of silicon carbide in the transition layer is greater than the volume percentage of silicon carbide in the bearing layer; and the functional layer comprises a silicon carbide / carbon / metal composite material.

[0020] The preparation method has simple steps, strong process reliability, high production efficiency, and can realize large-scale industrial production.

[0021] Optionally, the volume ratio of silicon carbide powder to carbon powder in the second slurry used to form the transition layer and the functional layer increases layer by layer along the stacking direction of the unit layer preforms.

[0022] Optionally, the volume ratio of silicon carbide powder to carbon powder in the second slurry used to form the transition layer and the functional layer increases layer by layer from 1:(4-9) to 10:0.

[0023] Optionally, based on the dry matter in the second slurry added with iron, the volume percentage of the iron powder is 15% to 30%.

[0024] The third aspect of the present application provides a braking system, including the carbon-ceramic brake disc provided in the first aspect of the present application, or including the carbon-ceramic brake disc obtained by the preparation method described in the second aspect of the present application. Due to the use of the carbon-ceramic brake disc provided by the present application, the braking system has a better braking effect, higher reliability, and longer service life.

[0025] Optionally, the braking system includes the carbon-ceramic brake disc, a brake caliper bracket, a brake caliper housing and a friction plate.

[0026] The fourth aspect of the present application provides a vehicle, comprising the braking system provided by the third aspect of the present application. Due to the braking system provided by the third aspect of the present application, the vehicle has good market competitiveness.

[0027] Optionally, the transportation vehicle includes a vehicle or an airplane; wherein the vehicle includes at least one of a car and a rail transit train. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A schematic diagram of a variation of the structure of the carbon-ceramic brake disc provided in the present application;

[0029] Figure 2 A schematic diagram of the structure of another variation of the carbon-ceramic brake disc provided in the present application.

[0030] Explanation of reference numerals: 100 - carbon ceramic brake disc; 10 - load-bearing layer; 20 - friction layer; 21 - transition layer; 22 - functional layer; 30 - unit layer. DETAILED DESCRIPTION

[0031] See also Figure 1 The embodiment of the present application provides a carbon ceramic brake disc 100, comprising a bearing layer 10 and a friction layer 20 disposed on two opposite sides of the bearing layer 10; the friction layer 20 comprises a transition layer 21 and a functional layer 22 stacked, and the transition layer 21 is disposed close to the bearing layer 10;

[0032] Among them, the bearing layer 10 includes carbon / silicon carbide material; the transition layer 21 includes a silicon carbide / carbon composite material, and the volume percentage of silicon carbide in the transition layer 21 is greater than the volume percentage of silicon carbide in the bearing layer; the functional layer 22 includes a silicon carbide / carbon / metal composite material; wherein the metal is a metal that can form a solid solution with carbon.

[0033] The bearing layer in the above carbon ceramic brake disc can provide sufficient toughness and mechanical support for the material, while the carbon fiber in the functional layer can provide it with a certain toughness, and the silicon carbide can provide hardness and wear resistance. In particular, when the brake system brakes, the friction plate in the brake system clamps the above carbon ceramic brake disc, and the metal in the friction plate is in direct contact with the functional layer of the carbon ceramic brake disc. At this time, the metal in the functional layer can produce adhesive friction with the metal material on the friction plate, thereby enhancing the friction coefficient between the functional layer and the friction plate without significantly increasing the density of the carbon ceramic brake disc, thereby facilitating the braking of the final brake disc and the reliability of the entire brake system, especially reducing the loss of the friction plate when braking at high speed, so the service life of the entire brake system can be extended. At the same time, because the presence of the transition layer can reduce the composition difference between the functional layer and the bearing layer, it can reduce the cracking caused by excessive stress of the final brake disc during the braking process, thereby extending the service life of the final brake disc itself and improving its reliability.

[0034] In addition, the presence of metal can also improve the thermal conductivity of the functional layer, so that the heat generated after braking can be quickly diffused in the functional layer, slowing down the heat concentration in the functional layer after braking, thereby further ensuring the reliability of the final brake disc and further extending its service life; and based on the property that metal can form a solid solution with carbon, when carbon is dissolved into the metal lattice, the hardness and strength of the metal can be appropriately improved, which is conducive to the performance of the carbon-ceramic brake disc. With the cooperation of the above-mentioned bearing layer, transition layer and functional layer, the carbon-ceramic brake disc can have both a long service life and high reliability.

[0035] Specifically, in an embodiment of the present application, the bearing layer 10 includes a carbon fiber reinforced carbon / silicon carbide composite material, wherein the carbon fiber is distributed as a reinforcing phase in a continuous phase of carbon material (e.g., deposited carbon) / silicon carbide. The transition layer 21 includes a carbon fiber reinforced silicon carbide / carbon composite material, specifically, a mixture of silicon carbide and carbon material as a continuous phase, and carbon fiber is distributed in the above continuous phase as a reinforcement. The functional layer 22 includes a carbon fiber reinforced silicon carbide / carbon / metal composite material, specifically, the functional layer 22 includes a continuous phase, the continuous phase includes a mixture of carbon material and metal, and silicon carbide material, and carbon fiber is distributed in the above continuous phase as a reinforcement. Among them, the mixture of carbon material and metal in the continuous phase of the functional layer may include: a solid solution formed by carbon and metal, and a mixture of the solid solution and carbon material. Alternatively, it may also include a solid solution formed by carbon and metal, and a mixture of the solid solution and metal, but is not limited to the above.

[0036] In some embodiments of the present application, the metal includes but is not limited to at least one of iron, titanium and zirconium. Iron, titanium and zirconium have a certain oxidation resistance, which is beneficial to prolonging the service life of the carbon-ceramic brake disc. Correspondingly, at this time, the functional layer may include a solid solution of carbon and iron, a solid solution of carbon and titanium, and a solid solution of carbon and zirconium.

[0037] In some embodiments of the present application, the metal is dispersed in the functional layer in the form of powder, and the particle size of the metal powder is in the range of 0.5μm to 20μm. For example, the particle size of the metal powder can be 0.8μm, 1.0μm, 2.0μm, 3.0μm, 4.0μm, 5.0μm, 8.0μm, 10.0μm, 12.0μm, 14.0μm, 15.0μm, 18.0μm, 19.0μm, 19.5μm, etc. Controlling the particle size distribution of the powder within the above range can improve the uniformity of the material distribution in the functional layer, further stabilize the wear resistance and thermal conductivity of the functional layer, and thus facilitate further improvement of the reliability and service life of the carbon ceramic brake disc.

[0038] In some embodiments of the present application, the volume percentage of the metal in the functional layer is 0.1% to 30%. For example, the volume percentage of the metal in the functional layer is 0.1% to 30.0%. In some specific embodiments, the volume percentage of the metal in the functional layer is 15% to 30%. In this way, it is beneficial to control the iron content in the functional layer within a suitable range, so that the functional layer finally obtained has both a high metal friction coefficient and good thermal conductivity, and the density of the entire carbon-ceramic brake disc is also controlled within a more suitable range, which is beneficial to the performance of its braking performance. For example, the volume percentage of the metal in the functional layer can be 0.1%, 0.5%, 1.0%, 2.0%, 5.0%, 8.0%, 10.0%, 12.0%, 15.0%, 18.0%, 20.0%, 22.0%, 25.0%, 28.0%, 30.0%, etc.

[0039] In some embodiments of the present application, the volume ratio of silicon carbide to carbon in the functional layer is greater than the volume ratio of silicon carbide to carbon in the transition layer. In this way, the silicon carbide concentration distribution in the friction layer can be further refined, thereby further weakening the material composition change from the bearing layer to the functional layer, further improving the uneven stress distribution or cracks caused by the large difference in composition between the friction layer and the bearing layer on the surface of the final carbon-ceramic brake disc, and further improving the reliability and service life of the final carbon-ceramic brake disc.

[0040] In some implementations of this application, please see Figure 2 The friction layer 20 includes n unit layers 30 stacked in layers, wherein the n unit layers include a unit layers constituting the transition layer 21 and b unit layers constituting the functional layer 22; n is a positive integer greater than or equal to 2, a and b are each independently a positive integer, and a+b=n; i+1 >I i ; Among them, I iRepresents the proportion of the volume of silicon carbide in the i-th unit layer in the sum of the volumes of silicon carbide and carbon; wherein the i-th unit layer is any one of the 1st unit layer to the (n-1)th unit layer, and the 1st unit layer is arranged close to the bearing layer, 1≤i≤n-1, and i is a positive integer. It can be understood that on the surface of the bearing layer, there are n stacked unit layers, and these n unit layers include a carbon fiber reinforced silicon carbide / carbon composite material unit layers stacked in sequence, and b carbon fiber reinforced silicon carbide / carbon / metal composite material unit layers, the a carbon fiber reinforced silicon carbide / carbon composite material unit layers constitute a transition layer, and the b carbon fiber reinforced silicon carbide / carbon / metal composite material unit layers constitute a functional layer; at the same time, in the above n unit layers, the proportion of the volume of silicon carbide in the sum of the volumes of silicon carbide and carbon increases layer by layer. In this way, when a>1, the gradient setting of silicon carbide and carbon content in the transition layer can be further refined (slowed down), and the volume content of each substance can be controlled layer by layer. The thermal mismatch problem caused by the different thermal expansion coefficients of silicon carbide and carbon fiber in the product after siliconization can be slowed down. At the same time, the thermal stress caused by the heating of the friction surface during braking is also alleviated, thereby further reducing the risk of cracking of the carbon-ceramic brake disc after repeated use and extending its service life; similarly, when b>1, the functional layer itself also has a gradient setting of silicon carbide and carbon content, and the hardness in the functional layer gradually decreases, which is beneficial to the stress conduction at the interface between the functional layer and the transition layer, and is also beneficial to reduce the risk of cracking of the carbon-ceramic brake disc after repeated use and extend its service life. In some specific embodiments, a>1, b>1, that is, the transition layer and the functional layer contain multiple unit layers at the same time. In some specific embodiments, b is a positive integer between 2 and 6, that is, the functional layer can contain 2, 3, 4, 5 or 6 unit layers. In some specific embodiments, a is a positive integer between 2 and 6.

[0041] In some embodiments of the present application, 5%≤I i+1 -I i ≤20%. In other words, in the n unit layers of the friction layer, the volume of silicon carbide accounts for a proportion of the sum of the volumes of silicon carbide and carbon. i The volume of silicon carbide increases from the first unit layer to the nth unit layer, and the difference between the sum of the volumes of silicon carbide and carbon between any two adjacent unit layers is independently between 5% and 20% (for example, the values ​​of I2-I1 and I3-I2 may be equal or different, and so on). i+1 -I iThe value of can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc. In this way, the gradient change of the material content in the friction layer can be controlled to be more uniform, and the gradient is set within a more appropriate range, which fully ensures that the gradient change of the silicon carbide content in the friction layer is small, and the thermal stress caused by the heat generated during friction is effectively alleviated. At the same time, the stress during braking is also evenly distributed in the friction layer with gradient changes, which fully reduces the risk of cracking of the brake disc and fully extends its service life.

[0042] In some embodiments of the present application, the thickness of the unit layer is independently in the range of 0.4 mm to 2.0 mm. In this way, it is beneficial to control the total thickness of the friction layer within a suitable range, and a sufficient and sufficiently gentle silicon carbide volume content gradient can be set within a smaller friction layer thickness range. Exemplarily, the thickness of the unit layer can be 0.40 mm, 0.45 mm, 0.50 mm, 0.55 mm, 0.60 mm, 0.65 mm, 0.70 mm, 0.75 mm, 0.80 mm, 0.85 mm, 0.90 mm, 0.95 mm, 1.00 mm, 1.10 mm, 1.20 mm, 1.30 mm, 1.40 mm, 1.50 mm, 1.60 mm, 1.70 mm, 1.80 mm, 1.90 mm, 2.00 mm, etc.

[0043] In some embodiments of the present application, the thickness of the friction layer is 3.0 mm to 6.0 mm. For example, the thickness of the friction layer can be 3 mm, 3.2 mm, 3.4 mm, 3.5 mm, 3.6 mm, 3.8 mm, 4.0 mm, 4.2 mm, 4.5 mm, 4.6 mm, 4.8 mm, 5.0 mm, 5.2 mm, 5.4 mm, 5.5 mm, 5.6 mm, 5.8 mm, 6.0 mm, etc. By controlling the thickness of the friction layer within the above range, the total thickness of the carbon-ceramic brake disc can be reduced while ensuring the braking performance of the carbon-ceramic brake disc, thereby greatly improving the market competitiveness of the carbon-ceramic brake disc.

[0044] In some embodiments of the present application, the thickness of the transition layer is 2.0 mm to 5.0 mm. For example, the thickness of the transition layer can be 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.0 mm, 3.1 mm, 3.2 mm, 3.3 mm, 3.4 mm, 3.5 mm, 3.6 mm, 3.7 mm, 3.8 mm, 3.9 mm, 4.0 mm, 4.1 mm, 4.2 mm, 4.3 mm, 4.4 mm, 4.5 mm, 4.6 mm, 4.7 mm, 4.8 mm, 4.9 mm, etc. Based on the gradient of the volume content of silicon carbide in the transition layer, the thickness of the transition layer can be controlled within the above range, which is beneficial to reducing the total thickness of the carbon-ceramic brake disc, and can ensure that the braking effect and reliability of the carbon-ceramic brake disc are good, and the service life is long.

[0045] In some embodiments of the present application, the thickness of the functional layer is 1.0 mm to 3.0 mm. For example, the thickness of the functional layer can be 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.0 mm, etc. Controlling the thickness of the functional layer within the above range also controls the thickness of the metal-containing part in the friction layer within a more appropriate range, which can ensure that the metal friction coefficient of the carbon-ceramic brake disc is high and can quickly conduct the heat generated by friction during braking, and can also ensure that the overall density of the carbon-ceramic brake disc is small, which is conducive to the performance of braking performance. At the same time, based on the volume content gradient setting of the silicon carbide of the above-mentioned unit layer, the functional layer can also be composed of an appropriate number of unit layers, which is conducive to the transmission of stress in the carbon-ceramic brake disc, and thus is conducive to the service life of the carbon-ceramic brake disc.

[0046] In some embodiments of the present application, the thickness of the bearing layer is 30.0 mm to 50.0 mm. For example, the thickness of the bearing layer can be 30.0 mm, 32.0 mm, 34.0 mm, 35.0 mm, 36.0 mm, 38.0 mm, 40.0 mm, 42.0 mm, 45.0 mm, 48.0 mm, 50.0 mm, etc. In this way, sufficient mechanical support can be provided for the friction layer, which is beneficial to the braking effect of the carbon ceramic brake disc.

[0047] The present application also provides a method for preparing a carbon-ceramic brake disc, comprising the following steps:

[0048] S01. Provide a carbon fiber preform, the carbon fiber preform includes carbon fiber impregnated with a first slurry, the first slurry contains carbon powder; at least one unit layer preform is formed on the surfaces of the opposite sides of the carbon fiber preform respectively, so that the unit layer preform is connected to the carbon fiber preform; wherein the unit layer preform includes a carbon fiber cloth; in the process of forming the unit layer preform, a second slurry is injected into the unit layer preform; the second slurry includes carbon powder and silicon carbide powder to obtain a first preform; in some embodiments of the present application, the above-mentioned unit layer preform includes a stacked carbon fiber unidirectional cloth and a carbon fiber mesh cloth, wherein the carbon fiber unidirectional cloth is placed close to the carbon fiber preform, and the mesh cloth and the unidirectional cloth can be connected to form a carbon fiber unit layer. In some specific embodiments, when forming multiple unit layer preforms, the arrangement directions of the carbon fibers in the carbon fiber unidirectional cloths in two adjacent unit layer preforms are different.

[0049] S02. Continue to form at least one unit layer preform on the opposite side surfaces of the first preform; wherein, during the formation process, a second slurry added with metal powder is injected into the unit layer preform to obtain a second preform; wherein, the metal powder is a metal powder that can form a solid solution with carbon; that is, the metal is a metal that can form a solid solution with carbon; in some embodiments of the present application, the metal powder includes but is not limited to at least one of iron powder, titanium powder and zirconium powder.

[0050] S03. After the second preform is carbonized, it is subjected to chemical vapor deposition carbon treatment, and then high-temperature heat treatment and siliconization treatment are performed in sequence to transform the carbon fiber preform into a bearing layer of carbon material / silicon carbide, transform the unit layer preform injected with the second slurry into a transition layer, and transform the unit layer preform injected with the second slurry added with metal powder into a functional layer, so as to obtain a carbon-ceramic brake disc; it can be understood that during the process of its transformation into the functional layer, carbon (for example, pyrolytic carbon, carbon powder, etc.) can penetrate into the metal powder to form a solid solution of carbon and metal; wherein the transition layer includes a silicon carbide / carbon composite material, and the volume percentage of silicon carbide in the transition layer is greater than the volume percentage of silicon carbide in the bearing layer; the functional layer includes a silicon carbide / carbon / metal composite material. Among them, it can be understood that in the siliconization reaction, in the unit layer preform, part of the carbon powder and part of the pyrolytic carbon in the second slurry react with silicon element to generate silicon carbide, another part of the carbon powder and another part of the pyrolytic carbon are still free carbon, and the silicon carbide generated by the above reaction will be included in the surface of the original silicon carbide powder (particles) in the second slurry together with the free carbon, and together form a continuous phase to form a transition layer; similarly, the above reaction also occurs in the unit layer preform containing metal, but the difference is that the silicon carbide generated by the reaction will be wrapped on the surface of the metal powder together with the free carbon, thereby forming a silicon carbide / carbon / continuous phase; and in the carbon fiber preform, the silicon element reacts with part of the carbon powder and part of the pyrolytic carbon brought in the first slurry, and the generated silicon carbide forms a continuous phase together with the unreacted carbon.

[0051] In the embodiment of the present application, during the above process, the carbon fiber still exists in the carbon-ceramic brake disc in the form of a reinforcement phase.

[0052] In the above preparation method, different slurries are injected into the carbon fiber products at different positions at the same time during the process of forming the unit layer preform. Compared with the prior art of directly siliconizing the carbon fiber blank, the silicon carbide concentration gradient in the final carbon-ceramic brake disc can be precisely controlled. At the same time, the depth of the metal-containing part can also be precisely controlled (that is, the thickness of the functional layer can be precisely controlled), so that multiple silicon carbide content gradients can be set in the carbon-ceramic brake disc, and a carbon-ceramic brake disc with a smooth surface friction layer and no cracks can be obtained.

[0053] The preparation method has simple steps, strong process reliability, high production efficiency, and can realize large-scale industrial production.

[0054] Some embodiments of the present application are summarized, in the above step S01 and step S02, the forming is independently selected from at least one of acupuncture and threading. For example, in step S01, at least one unit layer preform is needled or threaded on the two opposite sides of the carbon fiber preform. For example, in step S02, at least one unit layer preform is continued to be needled or threaded on the two opposite sides of the first preform.

[0055] In some embodiments of the present application, the volume ratio of silicon carbide powder to carbon powder in the second slurry used to form the transition layer and the functional layer increases layer by layer along the stacking direction of the unit layer preforms. It can be understood that here, from the second slurry in step S01 to the second slurry added with metal powder in step S02, the volume ratio of silicon carbide powder to carbon powder increases layer by layer along the stacking direction of the unit layer preforms. The following is a detailed description of one possible embodiment as an example: 9 unit preforms are formed on the surface of the carbon fiber preform to prepare the friction layer, wherein, starting from the first unit layer preform (the first unit layer preform close to the carbon fiber preform), the ratio of carbon powder to silicon carbide powder in the second slurry is controlled to be 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, 0:10 layer by layer, and starting from the seventh unit layer preform, metal is also added to the second slurry.

[0056] In some embodiments of the present application, the volume ratio of silicon carbide powder to carbon powder in the second slurry used to form the transition layer and the functional layer increases layer by layer from 1: (4-9) to 10: 0. In this way, multiple silicon carbide content gradients can be formed in the friction layer of the carbon-ceramic brake disc, and the gradients are set gently. Exemplarily, the volume ratio of silicon carbide powder to carbon powder in the second slurry used to form the transition layer and the functional layer can be increased layer by layer from 1: 4, 1: 5, 1: 6, 1: 7, 1: 8, 1: 9, etc. to 10: 0.

[0057] In some embodiments of the present application, the volume percentage of the metal powder is 15% to 30% based on the dry matter in the second slurry to which the metal powder is added. That is, based on the total volume of the carbon powder, silicon carbide powder and metal powder in the second slurry, the volume percentage of the metal powder is 15% to 30%. Exemplarily, the volume percentage of the metal powder can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, etc. In this way, it is beneficial to control the metal content in the functional layer within a suitable range, so that the functional layer finally obtained has both a high metal friction coefficient and good thermal conductivity, and the density of the entire carbon ceramic brake disc is also controlled within a more suitable range, which is beneficial to the performance of its braking performance.

[0058] In this application, in S01, the carbonization treatment refers to subjecting the second preform to high temperature treatment in a protective atmosphere. The carbonization treatment is to remove organic matter in the second preform (including but not limited to sizing agents on the surface of carbon fibers and organic matter in other raw materials), so as to avoid the organic matter from hindering the subsequent deposition of carbon in the second preform. Carbonization conditions known to those of ordinary skill in the art can be used, and this application does not limit this. In some specific embodiments, the temperature of the carbonization treatment is 850°C-1100°C.

[0059] In the present application, in S01, the chemical vapor deposition carbon treatment may be to introduce cracked carbon into the second preform by using a chemical vapor infiltration (CVI) process, wherein the parameters used in the CVI process may be any parameter conditions known in the art. Specifically, the implementation process of the chemical vapor deposition carbon treatment is generally as follows: using helium or hydrogen as a carrier and hydrocarbon gas (e.g., gaseous hydrocarbons) as a carbon source, at a certain temperature and pressure, the gaseous carbon source enters the interior of the second preform by diffusion, flow, etc., and undergoes a pyrolysis reaction due to thermal activation under the action of high temperature to generate pyrolytic carbon and deposit it on the fiber surface in the form of a coating, and finally the coatings overlap with each other to become a continuous phase in the material.

[0060] In the present application, in S02, high temperature heat treatment and siliconization treatment are any conditions known to those skilled in the art, and the present application does not impose any limit thereto. Among them, high temperature heat treatment is conducive to the subsequent infiltration of silicon into the carbon fiber preform.

[0061] In some embodiments of the present application, the particle size of the carbon powder is in the range of 0.5 μm to 20 μm, the particle size of the silicon carbide powder is in the range of 0.5 μm to 20 μm, and the particle size of the metal powder is distributed in the range of 0.5 μm to 20 μm. Exemplarily, the particle sizes of the carbon powder, silicon carbide powder, and metal powder can be independently 0.8 μm, 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 8.0 μm, 10.0 μm, 12.0 μm, 14.0 μm, 15.0 μm, 18.0 μm, 19.0 μm, 19.5 μm, etc. In this way, it is beneficial to obtain a uniform second slurry and to infiltrate the unit layer preform with the second slurry, thereby obtaining a carbon-ceramic brake disc with a uniform material composition within the layer.

[0062] The embodiment of the present application also provides a braking system, including the carbon ceramic brake disc provided in the embodiment of the present application, or including the carbon ceramic brake disc prepared by the preparation method provided in the embodiment of the present application. Due to the use of the carbon ceramic brake disc provided in the present application, the braking system has a better braking effect, higher reliability, and longer service life.

[0063] In some embodiments of the present application, the braking system includes a carbon-ceramic brake disc, a brake caliper bracket, a brake caliper housing, and a friction plate.

[0064] The embodiment of the present application provides a vehicle, including the braking system provided by the present application. Due to the braking system provided by the present application, the vehicle has good market competitiveness.

[0065] In some embodiments of the present application, the transportation vehicle includes a vehicle or an airplane; wherein the vehicle includes at least one of a car and a rail transit train.

[0066] The technical solution of the present application is further described in detail below with multiple embodiments.

[0067] Example 1

[0068] (1) Providing a carbon fiber preform, the carbon fiber preform includes carbon fiber impregnated with a first slurry, the first slurry contains carbon powder; needle punching a unit layer preform on two opposite sides of the carbon fiber preform respectively, so that the unit layer preform is connected with the carbon fiber preform; wherein the unit layer preform includes a stacked carbon fiber unidirectional cloth and a carbon fiber mesh cloth; and during the needle punching process, injecting a second slurry into the unit layer preform to obtain the first preform; the second slurry includes carbon powder and silicon carbide powder, wherein the mass ratio of the carbon powder to the silicon carbide powder is 8:2.

[0069] (2) continuing to needle-punch a unit layer preform on the opposite sides of the first preform; during the needle-punching process, injecting a second slurry (specifically, carbon powder: silicon carbide: iron powder in a volume ratio of 6:2:2) with iron powder added into the unit layer preform to obtain a second preform;

[0070] (3) After the second preform is subjected to carbonization treatment in sequence, chemical vapor infiltration treatment is then performed to introduce pyrolytic carbon into the second preform, and high-temperature heat treatment and siliconization treatment are then performed in sequence to obtain the carbon ceramic brake disc of Example 1. The thickness of the bearing layer is 35 mm, the thickness of the transition layer is 2 mm, the thickness of the functional layer is 2 mm, and the thickness of the single unit layer is 2 mm. In the functional layer, the volume percentage of iron powder is 15%.

[0071] Example 2

[0072] The only difference from Example 1 is that in step (2), in the second slurry, the volume ratio of carbon powder: silicon carbide: iron powder is 5:3:2.

[0073] Example 3

[0074] The only difference from Example 1 is that in step (1), three unit layer preforms are formed on the opposite side surfaces of the carbon fiber preform, and from the first unit layer preform to the third unit layer preform, the volume ratios of carbon powder to silicon carbide powder in the second slurry are 65:35, 60:40, and 55:45 (with a gradient of 5%).

[0075] In step (2), two unit layer preforms are formed on the opposite side surfaces of the first preform, and the volume ratios of carbon powder and silicon carbide powder in the second slurry are 50:50 and 45:55 (with a gradient of 5%) from the 4th unit layer preform to the 5th unit layer preform, respectively; and the second slurry also contains iron powder, and the volume percentage of the iron powder is 20% based on the dry matter in the second slurry to which iron is added.

[0076] In the final carbon-ceramic brake disc, the thickness of the bearing layer is 33 mm, the thickness of the transition layer is 3 mm, the thickness of the functional layer is 2 mm, and the thickness of the single unit layer is 1 mm.

[0077] Example 4

[0078] The only difference from Example 3 is that in step (2), the volume percentage of iron powder is 15% based on the dry matter in the second slurry to which iron is added.

[0079] In the final carbon-ceramic brake disc, the thickness of the bearing layer is 33 mm, the thickness of the transition layer is 3 mm, the thickness of the functional layer is 2 mm, and the thickness of the single unit layer is 1 mm.

[0080] Example 5

[0081] The only difference from Example 3 is that in step (2), the volume percentage of iron powder is 30% based on the dry matter in the second slurry to which iron is added.

[0082] In the final carbon-ceramic brake disc, the thickness of the bearing layer is 33 mm, the thickness of the transition layer is 3 mm, the thickness of the functional layer is 2 mm, and the thickness of the single unit layer is 1 mm.

[0083] Example 6

[0084] The only difference from Example 3 is that in step (2), the volume percentage of iron powder is 40% based on the dry matter in the second slurry to which iron is added.

[0085] In the final carbon-ceramic brake disc, the thickness of the bearing layer is 33 mm, the thickness of the transition layer is 3 mm, the thickness of the functional layer is 2 mm, and the thickness of the single unit layer is 1 mm.

[0086] Example 7

[0087] The only difference from Example 1 is that in step (1), three unit layer preforms are needled on the surfaces of the opposite sides of the carbon fiber preform, and from the first unit layer preform to the third unit layer preform, the volume ratio of carbon powder to silicon carbide powder in the second slurry is 85:15, 65:35, and 45:55 (gradient of 20%).

[0088] In step (2), two unit layer preforms are formed on the opposite side surfaces of the first preform, and the volume ratios of carbon powder and silicon carbide powder in the second slurry are 25:75 and 5:95 (with a gradient of 20%) from the 4th unit layer preform to the 5th unit layer preform, respectively; and the second slurry also contains iron powder, and the volume percentage of the iron powder is 20% based on the dry matter in the second slurry to which iron is added.

[0089] In the final carbon-ceramic brake disc, the thickness of the bearing layer is 33 mm, the thickness of the transition layer is 3 mm, the thickness of the functional layer is 2 mm, and the thickness of the single unit layer is 1 mm.

[0090] Example 8

[0091] The only difference from Example 1 is that in step (1), 7 unit layer preforms are formed on the opposite side surfaces of the carbon fiber preform, and the volume ratios of the carbon powder to the silicon carbide powder in the second slurry are 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, and 3:7 from the first unit layer preform to the seventh unit layer preform.

[0092] In step (2), unit layer preforms are formed on opposite side surfaces of the first preform, so that from the 8th unit layer preform to the 10th unit layer preform, the volume ratio of carbon powder to silicon carbide powder in the second slurry is 2:8, 1:9, and 0:10 respectively; and the second slurry also contains iron powder, and the volume percentage of the iron powder is 20% based on the dry matter in the second slurry to which iron is added.

[0093] In the final carbon-ceramic brake disc, the thickness of the bearing layer is 33 mm, the thickness of the transition layer is 3.5 mm, the thickness of the functional layer is 1.5 mm, and the thickness of the single unit layer is 0.5 mm.

[0094] Example 9

[0095] The only difference from Example 8 is that iron powder is added only to the second slurry of the 10th unit layer preform. In the finally obtained carbon ceramic brake disc, the thickness of the bearing layer is 36 mm, the thickness of the transition layer is 3 mm, the thickness of the functional layer is 0.5 mm, and the thickness of the single unit layer is 0.5 mm.

[0096] Example 10

[0097] The only difference from Example 8 is that iron powder is added from the second slurry of the fifth unit layer preform. In the carbon ceramic brake disc finally obtained, the thickness of the bearing layer is 30 mm, the thickness of the transition layer is 3 mm, the thickness of the functional layer is 3.5 mm, and the thickness of a single unit layer is 0.5 mm.

[0098] Embodiment 11

[0099] The difference from Example 8 is that in step (1), 8 unit layer preforms are formed on the opposite side surfaces of the carbon fiber preform respectively, and from the first unit layer preform to the eighth unit layer preform, the volume ratios of carbon powder to silicon carbide powder in the second slurry are 85:15, 81:19, 77:23, 73:27, 70:30, 66:34, 62:38, and 58:42 respectively;

[0100] In step (2), 5 unit layer preforms are formed on the opposite side surfaces of the first preform, and the volume ratios of carbon powder to silicon carbide powder in the second slurry from the 9th unit layer preform to the 12th unit layer preform are 50:50, 46:54, 42:58, and 38:62, respectively; and the second slurry also contains iron powder, and the volume percentage of the iron powder is 20% based on the dry matter in the second slurry to which iron is added.

[0101] In the final carbon-ceramic brake disc, the thickness of the bearing layer is 30 mm, the thickness of the transition layer is 4 mm, the thickness of the functional layer is 2.5 mm, and the thickness of the single unit layer is 0.5 mm.

[0102] Example 12

[0103] The difference from Example 8 is that in step (1), two unit layer preforms are formed on the opposite side surfaces of the carbon fiber preform, and the volume ratios of the carbon powder and the silicon carbide powder in the second slurry are 80:20 and 65:35 respectively from the first unit layer preform to the second unit layer preform;

[0104] In step (2), two unit layer preforms are formed on the opposite side surfaces of the first preform, and the volume ratios of carbon powder to silicon carbide powder in the second slurry are 60:40 and 35:65 respectively from the third unit layer preform to the fourth unit layer preform; and the second slurry also contains iron powder, and the volume percentage of the iron powder is 20% based on the dry matter in the second slurry to which iron is added.

[0105] In the final carbon-ceramic brake disc, the thickness of the bearing layer is 39 mm, the thickness of the transition layer is 1 mm, the thickness of the functional layer is 1 mm, and the thickness of the single unit layer is 0.5 mm.

[0106] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are set.

[0107] Comparative Example 1

[0108] The only difference from Example 8 is that no iron powder is added to the second slurry.

[0109] Comparative Example 2

[0110] A carbon fiber preform is provided, and pyrolytic carbon is introduced through carbonization and CVI, and high temperature treatment and siliconization treatment are performed in sequence to obtain a carbon ceramic brake disc.

[0111] Comparative Example 3

[0112] A carbon fiber preform is provided, and pyrolytic carbon is introduced through carbonization and CVI, and high temperature treatment and siliconization treatment are performed in sequence to obtain a carbon ceramic brake disc. In which, a mixture of Si and Fe is used in the siliconization treatment, and the volume percentage of Fe powder is 40%.

[0113] Performance test: The dynamic friction coefficient and wear rate of the carbon ceramic brake disc sample were tested using the MM-1000 friction tester. The effective friction surface of the test ring has an outer diameter of D75MM / inner diameter of 55mm, and a specific pressure of 98N / cm 2 , inertia is 3kgf.cm.s 2 The results are summarized in Table 1.

[0114] The surface samples were taken for shear strength test, and the test method was GB / T 15089-2001. The results are summarized in Table 1.

[0115] Table 1

[0116] Experiment number Wear loss μm / surface*times Friction coefficient Surface shear strength Example 1 0.7 0.43 12MPa Example 2 0.64 0.43 13MPa Example 3 0.73 0.49 12MPa Example 4 0.69 0.44 12MPa Example 5 0.80 0.51 12MPa Example 6 1.0 0.53 11MPa Example 7 0.73 0.48 10MPa Example 8 0.68 0.45 14MPa Example 9 1.1 0.53 9MPa Example 10 1.08 0.53 7MPa Embodiment 11 0.98 0.51 6MPa Example 12 0.88 0.49 13MPa Comparative Example 1 0.6 0.35 13MPa Comparative Example 2 0.61 0.37 5MPa Comparative Example 3 1.23 0.51 6MPa

[0117] It can be seen from the data in Table 1 that the main performance of the carbon-ceramic brake disc provided in the embodiment of the present application is significantly higher than that of the comparative brake disc. By comparing the data between the embodiments, it can be found that when the silicon carbide content in the functional layer is greater than that in the transition layer, it is more conducive to improving the surface shear strength of the brake disc and reducing the amount of wear. By comparing the data of Examples 3-6, it can be found that when the amount of metal powder added to the second slurry during preparation is within the range further suggested in the present application (that is, when the volume percentage of metal in the functional layer is within the range further suggested in the present application), it is more conducive to the performance of the carbon-ceramic brake disc. By comparing the data of Examples 8-12, it can be found that when the thickness of the functional layer and the thickness of the friction layer are within the range suggested in the present application, while ensuring a high friction coefficient, it is also beneficial to reduce the amount of wear and surface shear strength of the carbon-ceramic brake disc.

[0118] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A carbon ceramic brake disc, characterized in that: It comprises a bearing layer and a friction layer arranged on two opposite sides of the bearing layer; the friction layer comprises a transition layer and a functional layer arranged in a stacked manner, and the transition layer is close to the bearing layer; Wherein, the bearing layer comprises a carbon / silicon carbide composite material; the transition layer comprises a silicon carbide / carbon composite material, and the volume percentage of silicon carbide in the transition layer is greater than the volume percentage of silicon carbide in the bearing layer; the functional layer comprises a silicon carbide / carbon / metal composite material, wherein the metal is a metal that can form a solid solution with carbon.

2. The carbon ceramic brake disc according to claim 1, characterized in that: A volume ratio of the silicon carbide to the carbon in the functional layer is greater than a volume ratio of the silicon carbide to the carbon in the transition layer.

3. The carbon ceramic brake disc according to claim 1, characterized in that: The friction layer includes n unit layers stacked together, wherein the n unit layers include a unit layers constituting the transition layer and b unit layers constituting the functional layer; n is a positive integer greater than or equal to 2, a and b are each independently a positive integer, and a+b=n; I i+1 >I i ; Among them, I i Represents the proportion of the volume of the silicon carbide in the i-th unit layer in the sum of the volumes of the silicon carbide and the carbon; wherein the i-th unit layer is any one of the 1st unit layer to the (n-1)th unit layer, and the 1st unit layer is arranged close to the bearing layer, 1≤i≤n-1, and i is a positive integer.

4. The carbon ceramic brake disc according to claim 3, characterized in that: 5%≤I i+1 -I i ≤20%。 5. The carbon ceramic brake disc according to claim 3 or 4, characterized in that: The thickness of each of the unit layers is independently in the range of 0.4 mm to 2.0 mm.

6. The carbon ceramic brake disc according to any one of claims 1 to 5, characterized in that: In the functional layer, the volume percentage of the metal is 0.1% to 30.0%.

7. The carbon-ceramic brake disc according to any one of claims 1 to 6, characterized in that: The thickness of the friction layer is 3.0 mm to 6.0 mm.

8. The carbon-ceramic brake disc according to any one of claims 1 to 7, characterized in that: The thickness of the transition layer is 2.0 mm to 5.0 mm; the thickness of the functional layer is 1.0 mm to 3.0 mm; and the thickness of the bearing layer is 30.0 mm to 50.0 mm.

9. The carbon-ceramic brake disc according to any one of claims 1 to 8, characterized in that: The metal is dispersed in the functional layer in the form of powder, and the particle size of the powder is in the range of 0.5 μm to 20 μm.

10. The carbon-ceramic brake disc according to any one of claims 1 to 8, characterized in that: The metal includes at least one of iron, titanium and zirconium.

11. A method for preparing a carbon ceramic brake disc, characterized in that: The following steps are involved: (1) providing a carbon fiber preform, wherein the carbon fiber preform comprises carbon fiber impregnated with a first slurry, wherein the first slurry contains carbon powder; At least one unit layer preform is formed on two opposite sides of the carbon fiber preform, so that the unit layer preform is connected with the carbon fiber preform; wherein the unit layer preform comprises carbon fiber cloth; during the forming process, a second slurry is injected into the unit layer preform; the second slurry comprises carbon powder and silicon carbide powder, so as to obtain a first preform; (2) continuing to form at least one unit layer preform on the opposite side surfaces of the first preform; wherein, during the forming process, a second slurry containing metal powder is injected into the unit layer preform to obtain a second preform; the metal powder is a metal powder that can form a solid solution with carbon; (3) After the second preform is carbonized, it is subjected to chemical vapor deposition carbon treatment, and then high-temperature heat treatment and siliconization treatment are performed in sequence to transform the carbon fiber preform into a bearing layer of a carbon / silicon carbide composite material, transform the unit layer preform injected with the second slurry into a transition layer, and transform the unit layer preform injected with the second slurry added with metal powder into a functional layer, so as to obtain a carbon-ceramic brake disc; wherein the transition layer comprises a silicon carbide / carbon composite material, and the volume percentage of silicon carbide in the transition layer is greater than the volume percentage of silicon carbide in the bearing layer; and the functional layer comprises a silicon carbide / carbon / metal composite material.

12. The preparation method according to claim 11, characterized in that: The volume ratio of silicon carbide powder to carbon powder in the second slurry used to form the transition layer and the functional layer increases layer by layer along the stacking direction of the unit layer preform.

13. The preparation method according to claim 12, characterized in that: The volume ratio of silicon carbide powder to carbon powder in the second slurry used to form the transition layer and the functional layer increases layer by layer from 1:(4-9) to 10:

0.

14. The preparation method according to any one of claims 11 to 13, characterized in that: Based on the dry matter in the second slurry added with metal powder, the volume percentage of the metal powder is 15% to 30%.

15. A braking system, characterized in that: The brake system comprises a carbon-ceramic brake disc as claimed in any one of claims 1 to 10, or comprises a carbon-ceramic brake disc obtained by the preparation method as claimed in any one of claims 11 to 14.

16. A means of transport, characterized in that: The vehicle comprises a braking system as claimed in claim 15 .

Citation Information

Patent Citations

  • Carbon ceramic friction disks and process for their preparation

    CN103370558A

  • Ceramic-carbon-ceramic hybrid composite material

    CN107399117A

  • Carbon fiber reinforced carbon-silicon carbide gradient composite material, preparation method thereof and application of composite material

    CN109133963A

  • Ice pattern coating aluminum-plastic composite plate and preparation method thereof

    CN111993709A

  • Rapid preparation method of carbon-ceramic brake disc

    CN112707735A